The Belief in Outdoor Play and Learning - Karen Marie Eid Kaarby; Cato Tandberg (European Teacher Education Network, 2017)
Norwegian kindergartens traditionally use outdoor environments for play and learning also for the youngest children regardless of the season. This research examines the assumptions and priorities underlying teachers' work with movement and sensory experiences in Norwegian kindergarten and how parents value children's outdoor play. We also investigate the subject-specific background of the teachers. Findings indicate that a high priority is placed on outdoor play and learning in Norwegian kindergartens. Assumptions of children's well-being outdoors may seem like a hidden curriculum, and learning possibilities may not be recognized or fully used by kindergarten teachers.